El castillo de Alba no fue un castillo de naipes - González Fernández, María Luz; Vidal Encinas, Julio Manuel (Estudios humanísticos. Geografía, historia y arte, 2001)
Recent archaeological research on the Alba Castle have for the first time uncovered evidente of the topographical and constructive features of this castle, which was briefly described by M. Gómez Moreno at the beginning of the last century. This medieval fortification (IX-XII) was placed on the top of a large crest encircled by an impressive wall and other defensive works. The situation and characteristics of this castle refute those which was recoginized by L. Avelino Gutiérrez as ’Castillo de Alaba’ in "El Bufo", an ensemble of ephemeral structures which probably to relate to shepherd huts, sheep enclosures, or defensive occurrences (breastworks) from the Spanish Civil War (1936-1939).